How Adequate and Efficient are Regulations on Corporate Social Responsibility and Social Reporting? Evidence from the Nigeria Telecommunication Industry - L, Raimi; A, Aljadani; A.O, Fadipe; I.A., Adeleke (Asian Journal of Empirical Research, 2014)
Retrospectively, agitation by multiple stakeholders in Nigeria for increased social involvements from multinational oil companies (MNOCs) and deregulation policy brought corporate social responsibility (CSR) and social reporting (SR) to limelight. In spite of these two critical issues, theoretical and empirical studies on adequacy and effectiveness of regulations on CSR and SR are few. Consequently, this exploratory paper examines the adequacy of regulations on CSR and SR in the Nigerian telecommunication industry. Judging by the focus of the paper, the legitimacy theory provides underpinning for the discourse. The authors employ qualitative research method strictly relying on documentary/archival sources. The findings indicate that Nigeria has adequate regulations (direct and indirect) on CSR and SR, and there are adequate regulatory agencies created to ensure compliance. Furthermore, the regulations are efficient based on evidence of social reporting of CSR programmes and projects in the annual reports and websites of the telecommunication companies. The paper concludes that these findings are tentative and require empirical investigation for their validity.